Peran Jintan Hitam (Nigella sativa) Sebagai Pengobatan Diabetes Mellitus - Intan Nanda Rezeki (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Abstract Diabetes mellitus is a disease characterized by an increase in glucose in the bloodand occurs when the pancreas does not produce insulin or when the body cannot effectivelyuse insulin. The results of Indonesia Basic Health Research in 2018, showed the prevalence ofDM in Indonesia has increased. This is caused by unchanging risk factors such as sex, age, andgenetic factors, the second is risk factors that can be changed such as smoking habits,education level, physical activity, alcohol consumption, body mass index. Management of ituses the four pillars such as educational management, lifestyle modification, exercise and theuse of anti-diabetes drugs. However, herbal medicine is currently being developed to helpovercome this degenerative disease in order to reduce the prevalence with using black cumin. Black cumin is a plant that is high in fiber with a low glycemic index and contains highnutritional value. Black cumin can be processed into powder, extract or oil. Antidiabeticmechanisms of cumin seeds through the protective effect of beta cells on oxidative stress,induction of cell-â proliferation, reducing MDA levels in pancreatic tissue, decreasingplasma levels of the hormone leptin, increasing Glut-4 expression and decreasinggluconeogenesis in the liver.